2013
DOI: 10.1109/tse.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Privacy and Utility in Cross-Company Defect Prediction

Abstract: Abstract-Background: Cross-company defect prediction (CCDP) is a field of study where an organization lacking enough local data can use data from other organizations for building defect predictors. To support CCDP, data must be shared. Such shared data must be privatized, but that privatization could severely damage the utility of the data. Aim: To enable effective defect prediction from shared data while preserving privacy. Method: We explore privatization algorithms that maintain class boundaries in a datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 52 publications
0
88
0
Order By: Relevance
“…CPDP is useful because for many companies that are relatively small or have new products, local data may not be readily available. With the use of better selection tools for training data and transfer learning techniques, researchers found it possible to predict defects for "data starved" software projects by using data from external sources [16]- [24].…”
Section: Transfer Learning and Prediction Modelsmentioning
confidence: 99%
“…CPDP is useful because for many companies that are relatively small or have new products, local data may not be readily available. With the use of better selection tools for training data and transfer learning techniques, researchers found it possible to predict defects for "data starved" software projects by using data from external sources [16]- [24].…”
Section: Transfer Learning and Prediction Modelsmentioning
confidence: 99%
“…Turhan et al showed that if we use all the data from a Training Data Set (TDS) -an aggregate of multiple data-sets, then the resulting defect predictor will have excessive false alarms [2]. A more recent study by Peters et al [12] demonstrated that if we used all the data from a TDS, then false alarms and recall would be low.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐project fault prediction refers to predicting faults in a project using prediction models trained from historical data of other projects . In recent years, we have witnessed a lot of interest in developing new CPFP methods.…”
Section: Related Workmentioning
confidence: 99%